Forensic investigation on the high failure rate of civil engineering solid mechanics course / Siong Wee Lee … [et al.] - Lee, Siong Wee; Jamal, Mohammad Hazizi; Hasbullah, Mohd Amran; Mohamed Ibrahim, Mohd Johan; Mohammad, Shahrul Nizam; Haron, Hairol Anuar (Universiti Teknologi MARA, 2021)
The attainment of program outcomes for Solid Mechanic course offered to the Diploma in Civil Engineering students is evaluated. It was found that most of the students were incapable to demonstrate graduate attributes which applying knowledge of mathematics, natural science and engineering fundamentals and the ability to analyse engineering problems. Therefore, this study investigates the impact of physics and maths scores on the students’ performance of solid mechanics. Analysis of the previous results in physics and maths shows that there is a clear link between students’ fundamentals knowledge and the understanding of solid mechanics. Meanwhile, this study also aims to find out the root causes that led to the high failure rate of solid mechanics. A quantitative method was employed and a total of 180 students responded to the survey. Results of survey indicate that most of the students perceived that they had limited time to gain deep understanding of the course and they could not visualise the complex problems in solid mechanics. Majority of the students admitted that they did not manage to solve all questions during their final exam, and they were indeed not well prepared for it. Hence, the problem of high failure rate is feasible to be solved provided both lecturers and students making efforts in striving the success of this course.